Fenomen przekładu w postjugosłowiańskiej literaturze emigracyjnej - Majdzik-Papić, Katarzyna (Przekłady Literatur Słowiańskich, 2023)
The article presents the strategies for describing the phenomenon of translation in the post-Yugoslav literature of exile, referring to the concept of born translated literature by R.L. Walkowitz and perception of the role of translation in contemporary culture by B. Bachmann-Medick and Mieczysław Dąbrowski. The author presents selected translation strategies of post-Yugoslav writers who play the role of their own translators and describe the experience of otherness, exile and translation.